The Sea in the Contemporary Syrian Short Story - Maroushiah, Muhammad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This paper seeks to present a conception of the sea and its effective role in the contemporary Syrian short story through a study of the works of a number of short story tellers who travelled at sea in search for mysteries of life to gain an understanding of the universe and explore the suffering of coastal residents. This conception is manifested in the short story writings by Abul Kader Rabe’a, Muhsen Yousef, Muhammad Smeer Jua’ra and others. The sea in the short story represents human concerns and the interdependent relationship between man and the sea. Each writer in his own way moves as a result of suffering from the private concerns to the national concerns. This is the center of Muhsen Yousef’s stories through a heroic resistance and bitter struggles with the powers of evil aliened with internal powers that have attempted to control the nation’s coasts. The Arab resistant triumphs over the powers of evil in a heroic epic and forces the powers to withdraw in defeat.